Analysis of Marketing Mix on Patient Satisfaction at General Hospital, Banda Aceh City - Muhammad Andriansyah; Irwan Saputra; Nasrul Zaman; Said Usman; Reza Fahlevi (International Journal of Medical Science and Public Health Research, 2025)
Law Number 44 of 2009 concerning Hospitals regulates that hospitals as health service facilities must carry out various service activities, including individual and comprehensive services, which include outpatient, inpatient, and emergency services. This study aims to analyze the marketing mix on patient satisfaction at Meuraxa Hospital, Banda Aceh City. This type of observational research uses a cross-sectional design. The population in this study included all inpatients and outpatients at Meuraxa Hospital, Banda Aceh City with a sample size of 173 patients. The statistical analysis used is Partial Least Square with smartPLS 4.0. There is a significant relationship between product (t = 7.313, p value = 0.000), price (t = 6.700, p-value = 0.004), place (= 3.292, p-value = 0.001), promotion (t = 2.160, p value 0.031), health workers (t = 6.762, p value 0.006), physical appearance (t = 7.404, p value 0.000), and service process (t = 7.905, p value 0.000) with patient satisfaction, then there is a relationship between product (t = 7.486, p value = 0.000) and place (t = 3.346, p value = 0.001) with price at RSUD Meuraxa Kota Banda Aceh, then there is a relationship between health workers and the service process (t = 3.129, p value = 0.002) with the service process at RSUD Meuraxa Kota Banda Aceh. The factor that most influences patient satisfaction is the service process at Meuraxa General Hospital Banda Aceh City with T statistics 7.905 (p-value 0.000). Product, price, place, promotion, health workers, physical appearance and service process are significantly related to patient satisfaction, then product and place are significantly related to price, and the health worker factor is significantly related to the service process. The service process is the most dominant factor affecting patient satisfaction is the service process at Meuraxa Hospital, Banda Aceh City.